Mood disturbance during cycling performance at extreme conditions - Lane, A. M.; Whyte, G. P.; Shave, R.; Bareny, S.; Stevens, M.; Wilson, M. (Journal of Sports Science & Medicine, 2005)
The purpose of the study was to investigate the effects of extreme environments on mood state changes in hypoxic conditions and cold conditions in comparison to baseline conditions. The research design involved participants completing a two-hour stationary cycle ergometer ride at a simulated altitude of 2,500 metres, O°C, and normal laboratory conditions at a pace equivalent of lactate threshold. Eight male elite cyclists (Age: M = 26.23 yrs., SD = 6.74) completed the hypoxia- normal cycling trials. Ten male highly trained cyclists (Age: M = 23.34 yrs., SD = 5.45) participated in the cold-normal trials. Mood was assessed before, after one hour, and after two hours using the 24-item Brunel Mood Scale. MANOVA results indicated no significant interaction effect for mood changes over time by environment condition (Wilks' Lambda = .73, p = .32, Eta2 = .05), a significant main effect for mood changes over time (Wilks' Lambda = .61. p < .001, Partial Eta2 = .15) and a significant main effect for differences in mood by condition (Wilks' Lambda = .72, p < .000, Partial Eta2 = .15). Results indicated that increased anger, depression and fatigue were associated with performing at altitude, particularly after two hours of exercise. Collectively, results lend support to the notion that altitude is associated with negative mood states, although it should be noted that environment conditions did not affect the change in mood states over time. We suggest that further research is needed to explore mechanisms that individuals use to regulate negative mood during strenuous exercise.